A Quantitative Situational Awareness Model of Pilot. Issue 1 (June 2014) - Shuang, Liu; Xiaoru, Wanyan; Damin, Zhuang
The pilot's situational awareness (SA) mainly depends on the perception, understanding and prediction of the information obtained from the man-machine display interface, therefore there is an intrinsic link between the display interface design and the level of pilot's SA. A quantitative SA model, which considers the influence of information importance on SA, the characteristics of human cognition and the Bayesian conditional probability theory, was proposed based on the attention allocation model built previously. This model was expected to be used to predict the pilot's SA levels under different task conditions. In order to verify the validity of the SA model, 20 volunteers were recruited to perform the instrument supervision tasks in four kinds of task, at the same time, Situation Awareness Global Assessment Technique (SAGTA), 3-dimensional Situational Awareness Rating Technique (3-D SART), and eye movement measurement were adopted for the evaluation of SAs. The experimental results reveal that, the SAGAT is the most effective approach to measure the level 2 SA, showing that the correct rate of SAGAT has the most similar changing trend with the task performance, and the SA model is validated since the changing trend of SA predicted by the model is highly correlated with the measurement indices.